Guidelines for Techno-Economic Analysis of Adsorption Processes - Danaci, David; Webley, Paul A.; Petit, Camille (Frontiers in Chemical Engineering, 2021)
Techno-economic analyses (TEAs) of CO2 capture technologies have risen in popularity, due to growing interest in meeting CO2 emissions reduction targets. Adsorption processes are one of the technologies proposed for CO2 capture, and although difficult, standardisation of TEAs for adsorption should be attempted. The reason is that TEAs are often referred to as input data to other forms of modelling, to guide policy, and act as summaries for those unfamiliar with adsorption processes. Herein, we discuss the aspects that should be considered when conducting TEAs for CO2 adsorption processes, we present the implications of choices made at the TEA stage and offer guidance on best practice. Overall, our aim is to make TEAs of adsorption processes more widely accessible to the adsorption community, and also more generally to communities engaged in the evaluation of CCS technologies.